CML8, an Arabidopsis Calmodulin-Like Protein, Plays a Role in Pseudomonas syringae Plant Immunity. (10th November 2016) - Zhu, Xiaoyang; Robe, Eugénie; Jomat, Lucile; Aldon, Didier; Mazars, Christian; Galaud, Jean-Philippe
Abstract : Calcium is a universal second messenger involved in various cellular processes including plant development and stress responses. Its conversion into biological responses requires the presence of calcium sensor relays such as calmodulin (CaM) and calmodulin-like (CML) proteins. While the role of CaM is well described, the functions CML proteins remain largely uncharacterized. Here, we show that Arabidopsis CML8 expression is strongly and transiently induced by Pseudomonas syringae, and reverse genetic approaches indicated that the overexpression of CML8 confers on plants a better resistance to pathogenic bacteria compared with wild-type, knock-down and knock-out lines, indicating that CML8 participates as a positive regulator in plant immunity . However, this difference disappeared when inoculations were performed using bacteria unable to inject effectors into a plant host cell or deficient for some effectors known to target the salicylic acid (SA) signaling pathway. SA content and PR1 protein accumulation were altered in CML8 transgenic lines, supporting a role for CML8 in SA-dependent processes. Pathogen-associated molecular pattern (PAMP) treatments with flagellin and elf18 peptides have no effects on CML8 gene expression and do not modify root growth of CML8 knock-down and overexpressing lines compared with wild-type plants. Collectively, our results support a role for CML8 in plant immunity against P. syringae.